First report of Fusarium subglutinans (Wollenw. & Reinking) (1983) as a causative agent of leaf spot disease on broad bean Vicia faba L. in Iraq - Baidaa G. Ofi; Mohammed H. Abass; Yehya A. Salih (University of Thi-Qar Journal of agricultural research, 2023)
Broad bean (Vicia faba L.) is one of the most common vegetable crops in Iraq; cultivated in many areas. Broad bean production has been affected significantly by several diseases caused by either bacteria or fungi; among these pathogens Fusarium have a direct impact on faba beans production. The current study was conducted at the laboratories of the College of Agriculture - University of Basrah to identify the fungal pathogens of broad bean leaf spot disease. Isolation of the fungal pathogen was performed on PDA and PCA media; the morphological and microscopic identification revealed the identity of Fusarium subglutinans, followed a molecular diagnosis by ITS universal primers (ITS1 and ITS4) with a similarity percentage of 99%; the gene sequence was deposited at NCBI as LC769974. Experimental tests confirmed the pathogen's capability to infect the vegetative system of the broad bean plants. This is the first recorded of F. subglutinans being identified as the cause of leaf spotting on broad bean plants, making it a notable discovery in both Iraq and globally.